Clean Drinking Water Access In Egypt’s Marginalized Areas: A Case study of Life From Water Foundation - Mansy, Walaa Nasser (AUC Knowledge Fountain, 2024)
Egypt currently suffers from marked water scarcity due to its vulnerability to climate change, uneven water distribution, degradation of water quality, and misuse of water resources in rural and peri-urban areas, leading to health risks and poor hygiene. It is worth noting that Egypt is at a turning point in facing the impacts of climate change action and continuing its national development of water resources to ensure access to safe drinking water and sanitation services to cover the rapid demands of all beneficiaries. However, there is a vulnerability in many marginalized rural and peri-urban areas as they still face a lack of adequate water infrastructure and high levels of poverty with significant leakage, inefficient pumping, and degraded water quality. This study aims to bridge possible disconnects between the government's macro policy aims and NGOs in finding solutions for a comprehensive regulatory framework integrating the environmental and development needs of clean water and sanitation services. Based on a qualitative approach, this study used semi-structured interviews and fieldwork observation to collect the perceptions of various policymakers, practitioners, and beneficiaries to understand the underlying structures of the opportunities, challenges, and perspectives on policy implementation for clean water provision with engaging stakeholders harmonizing water supply and demand by using water efficiently. So, this study would be the conceptual framework of the integrated water management approach, including the ability to develop further action to achieve adequate water supply services with proper quality and quantity for rural and peri-urban areas. In this study, this conceptual framework was aligned with the implementation of Donald Van Meter and Carl Van Horn model for specificizing the relationships of bringing civil society participation in rural areas into dialogue to combine policy dialogue and technicality with considering the intervention of the social, economic, political, and environmental aspects. Accordingly, the interviews` feedback identified that the NGOs partially work as mediators with the government in implementing their water development plan to install water tap connections inside households for deserving families. However, there are deep-rooted challenges in delivering water governmental services in the presence of institutional constraints in having the three-way relationship between the state, NGOs (water providers), and citizens due to centralization, overlapping mandates, and limited state capacities in water and sanitation service delivery. The study recommends the implementation of a holistic legislative framework for the inter-relationships between the different levels of the actors to consider cross-sector strategic engagement for sustainable water infrastructure projects. Additionally, the study recommends ensuring water quality management, increasing the investment in capacity building, and raising awareness. KEYWORDS: Water scarcity, water infrastructure, multi-stakeholder governance water quality.